University Academic Jockeys and The Law in Islam - Sugeng Santoso; Ivan Hadi Prawira Negara; Putu Yoga Satya Pratama (Yayasan Pesantren Mahasiswa An-Nur, 2023)
This research aimed to describe the existence of university academic jockeys and the law status in Islam. This research used qualitative-descriptive techniques. The research method was utilized to characterize and characterize the subjects raised. The subjects for this research were academic jockey service providers and consumers at university, with a total of eight service providers and twenty-five service users. Observations and questionnaires were employed to obtain data. Meanwhile, Miles and Huberman’s interactive data analysis model was operated for data analysis, consisting of three stages: data reduction, data display, and verification. The findings of this research indicate that: (1) there are numerous types of jockey services available, ranging from the thesis, journal, daily tasks, and conference papers; (2) the income earned by service provider respondents are dominated by a range of IDR 1.000.000 to IDR 3.000.000/per month, the majority of them do not feel guilty about performing this work; and (3) in Islam, academic jockey activities are prohibited, as there is an agreement aimed at cheating and both parties suffer negative impacts; (4) academic jockeying has several negative impacts, including the erosion of higher education's integrity.